Migratory bats are attracted by red light but not by warm‐white light : Implications for the protection of nocturnal migrants - Voigt, Christian C.; Rehnig, Katharina; Lindecke, Oliver; Pētersons, Gunārs (Freie Universität Berlin, 2018)
The replacement of conventional lighting with energy‐saving light emitting diodes (LED) is a worldwide trend, yet its consequences for animals and ecosystems are poorly understood. Strictly nocturnal animals such as bats are particularly sensitive to artificial light at night (ALAN). Past studies have shown that bats, in general, respond to ALAN according to the emitted light color and that migratory bats, in particular, exhibit phototaxis in response to green light. As red and white light is frequently used in outdoor lighting, we asked how migratory bats respond to these wavelength spectra. At a major migration corridor, we recorded the presence of migrating bats based on ultrasonic recorders during 10‐min light‐on/light‐off intervals to red or warm‐white LED, interspersed with dark controls. When the red LED was switched on, we observed an increase in flight activity for Pipistrellus pygmaeus and a trend for a higher activity for Pipistrellus nathusii. As the higher flight activity of bats was not associated with increased feeding, we rule out the possibility that bats foraged at the red LED light. Instead, bats may have flown toward the red LED light source. When exposed to warm‐white LED, general flight activity at the light source did not increase, yet we observed an increased foraging activity directly at the light source compared to the dark control. Our findings highlight a response of migratory bats toward LED light that was dependent on light color. The most parsimonious explanation for the response to red LED is phototaxis and for the response to warm‐white LED foraging. Our findings call for caution in the application of red aviation lighting, particularly at wind turbines, as this light color might attract bats, leading eventually to an increased collision risk of migratory bats at wind turbines.